1991
DOI: 10.1159/000195905
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Hypoxia in Unilateral Diaphragmatic Paralysis

Abstract: Pulmonary function has been studied extensively in patients with unilateral diaphragmatic paralysis (UDP), but there is scarce information regarding the respiratory function during sleep in this condition. We therefore studied pulmonary function in 12 patients with UDP when awake and when asleep. Diaphragmatic dysfunction was confirmed by the demonstration of low maximal transdiaphragmatic pressures in most of our patients; paradoxical gastric pressure swing was observed in 6 patients. There was a restrictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…An early study by DOUGLAS and CLAGETT [33] found 10-24% of patients with hemidiaphragm paralysis to be breathless. PATAKAS et al [15] described 12 patients with nocturnal hypoxia and presumed UDP, but characterised the patients insufficiently for accurate diagnosis of unilateral phrenic nerve dysfunction. As shown in the present study, only 17 out of 39 patients who were clinically suspected to have UDP actually had unilateral involvement when assessed with electrophysiological tests of the phrenic nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early study by DOUGLAS and CLAGETT [33] found 10-24% of patients with hemidiaphragm paralysis to be breathless. PATAKAS et al [15] described 12 patients with nocturnal hypoxia and presumed UDP, but characterised the patients insufficiently for accurate diagnosis of unilateral phrenic nerve dysfunction. As shown in the present study, only 17 out of 39 patients who were clinically suspected to have UDP actually had unilateral involvement when assessed with electrophysiological tests of the phrenic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported disturbed sleep, inadequate ventilation during sleep and daytime sleepiness caused by diaphragm dysfunction [8,11], while others have found little impact on the normal sleep pattern unless there is additional load on the ventilatory system [9,10,14]. Previous studies either did not focus on UDP (had mixed populations of BDP and UDP [8,9] or exclusively BDP [5,11] patients), did not distinguish between REM and non-REM (NREM) sleep-associated sleepdisordered breathing (SDB) [10], did not characterise the subjects other than with noninvasive measurements [15] or studied animal models. Therefore, the studies that did not perform invasive respiratory muscle tests did not test a homogenous population of UDP patients and it is likely that the different results reflect the heterogeneity of the patients studied, in terms of weakness and ventilatory load.…”
mentioning
confidence: 99%
“…Subjects with isolated diaphragmatic paralysis are particularly prone to nocturnal desaturation during REM sleep [38], even with only unilateral involvement [46]. Although few detailed polysomnographic studies have been performed in such patients, REM sleep [46] and slow-wave sleep (SWS) are likely to be reduced [38,46].…”
Section: Isolated Diaphragmatic Paralysismentioning
confidence: 99%
“…Although few detailed polysomnographic studies have been performed in such patients, REM sleep [46] and slow-wave sleep (SWS) are likely to be reduced [38,46]. Daytime respiratory failure is unusual with isolated bilateral diaphragmatic paralysis unless there is coexisting intrinsic lung disease (e.g.…”
Section: Isolated Diaphragmatic Paralysismentioning
confidence: 99%
“…Whilst the majority of patients have obstructive sleep apnoea (OSA) [4,5], other causes of SDB may similarly cause health problems [6][7][8][9][10][11][12]. In the present study, we considered the group of patients with neuromuscular disease (NMD) who are affected by SDB because of weakness of the respiratory muscles [9,[13][14][15][16][17][18] influenced by posture and sleep stage [9,19] and who do not necessarily present with symptoms, such as daytime fatigue, that are measured by the Epworth Sleepiness scale (ESS) [20].…”
mentioning
confidence: 99%